Late diagnosis of hiV before and during the CoVid-19 pandemic: preliminary insights from an infectious diseases Unit in Apulia - Bruno, Giuseppe; Buccoliero, Giovanni Battista (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
During the COVID-19 pandemic, many HIV outpatient clinics were temporarily closed or their activities were reduced. Similarly, many infectious disease wards were converted into COVID-19 Units. Thus, an increase in late HIV diagnoses was expected due to reduced access to testing, screening services and consultation with HIV infection specialists. A higher rate of late HIV diagnoses was reported during the COVID-19 pandemic compared with the period before COVID-19. We analyzed all consecutive individuals newly diagnosed with HIV in our Center between January 1, 2017 and September 30, 2022. We did not observe differences in terms of late HIV diagnoses and AIDS between the two periods.